If Bacterial Endocarditis Wasn’t Enough, Here’s A Fungal One! A Rare Case Report - Fiúza, Pedro; Eusébio, Sofia; Soares, Raquel; Conchinha, André; Cunha, Sofia; Lopes, Adriana; Nascimento, Paula; Tosatto, Valentina (International Journal of Innovative Research in Medical Science, 2024)
An 80-year-old male, autonomous, with a history of cardiovascular risk factors, underwent aortic bioprosthesis placement for symptomatic severe aortic stenosis. He presented with acute bacterial endocarditis of the aortic valve prosthesis caused by methicillin-resistant Staphylococcus epidermidis (MRSE). The patient also had a pacemaker for atrial fibrillation and required catheter replacement due to infectious vegetation. Admitted one year after a previous episode of bacterial endocarditis, he exhibited fever of unknown origin, prostration, anorexia, and elevated inflammatory markers. Empirical treatment was initiated with ceftriaxone, gentamicin, and vancomycin. Hemocultures revealed Candida metapsilosis, leading to the addition of caspofungin. Transesophageal echocardiography showed vegetations on the bioprosthesis but none on the pacemaker catheter. He spent 103 days in the hospital, including intensive care for renal dysfunction. Following persistent fungemia, antifungal therapy was switched to liposomal amphotericin B. Haemocultures were sterilized 38 days after treatment initiation. The patient was discharged on lifelong itraconazole, with no periprosthetic complications, highlighting a rare case of recurrent fungal endocarditis following bacterial infection.